The de-sign of design - Azlaini Haji Abdul Aziz,; Masran bin Saruwono, (Penerbit UKM, 2008)
“Design” is a term which may be commonly used but could be interpreted differently. It is being used extensively in most areas of our everyday lives ranging from the arts to the sciences. The word “design” is indeed “sacred” to a designer. Perhaps this is because it provides reasons for the existence of the designer. Designers give “life” to objects of design through the generation of meaning. The paper focuses on design within the locale of the arts in Malaysia, which includes furniture design. It attempts to give critical overview on the adaptations of identity into design in Malaysia, through the approach of “semiotics”. Further, it explores the “meaning generation processes” within post-modern designs in Malaysia. The paper concludes by urging Malaysian designers to rethink their design approaches so that our rich culture will be reflected in the objects of design in the realm of globalization